The Role of Trust in Organizational Settings - Dirks, Kurt T.; Ferrin, Donald L. (Organization Science, 2001)
Numerous researchers from various disciplines seem to agree that trust has a number of important benefits for organizations, although they have not necessarily come to agreement on how these benefits occur. In this article, we explore two fundamentally different models that describe how trust might have positive effects on attitudes, perceptions, behaviors, and performance outcomes within organizational settings. In the first section of the article, we examine the model that has dominated the literature: Trust results in direct (main) effects on a variety of outcomes. In the second section of the article we develop an alternative model: Trust facilitates or hinders (i.e., moderates) the effects of other determinants on attitudinal, perceptual, behavioral and performance outcomes via two distinct perceptual processes. Lastly, we discuss the conditions under which each of the models is most likely to be applicable. The theory is supplemented with a review of empirical studies spanning 40 years regarding the consequences of trust in organizational settings. The theoretical framework presented in this article provides insight into the processes through which trust affects organizational outcomes, provides guidance to researchers for more accurately assessing the impact of trust, provides a framework for better understanding past research on the consequences of trust, and suggests ways that organizational settings can be modified to capitalize on high levels of trust or mitigate the effects of low levels of trust.